Devic’s neuromyelitis optica: a critical review - Lana-Peixoto,Marco Aurélio (2008)
Devic's neuromyelitis optica (NMO) is an idiopathic inflammatory demyelinating and necrotizing disease characterized by predominant involvement of the optic nerves and spinal cord. In Asian countries relapsing NMO has been known as opticospinal multiple sclerosis. It has long been debated if NMO is a variant of multiple sclerosis (MS) or a distinct disease. Recent studies have shown that NMO has more frequently a relapsing course, and results from attack to aquaporin-4 which is the dominant water channel in the central nervous system, located in foot processes of the astrocytes. Distinctive pathological features of NMO include perivascular deposition of IgG and complement in the perivascular space, granulocyte and eosinophil infiltrates and hyalinization of the vascular walls. These features distinguish NMO from other demyelinating diseases such as MS and acute demyelinating encephalomyelopathy. An IgG-antibody that binds to aquaporin-4, named NMO-IgG has high sensitivity and specificity. Magnetic resonance imaging (MRI) studies have revealed that more frequently there is a long spinal cord lesion that extends through three or more vertebral segments in length. Brain MRI lesions atypical for MS are found in the majority of cases. Treatment in the acute phase includes intravenous steroids and plasma exchange therapy. Immunosupressive agents are recommended for prophylaxis of relapses.